The Internalization of Prophetic Values in Regional Financial Reporting Practices: A Behavioral Accounting Perspective - Muhammad Haris Subangkit; Muhammad Roihan; Mashudi Mashudi (The Future of Education Journal, 2026)
This study aims to analyze the implementation of prophetic values in regional financial management practices from a behavioral accounting perspective, with a particular focus on the preparation of the Notes to the Financial Statements (CaLK). The study is motivated by the persistent challenges in regional financial management, including limited transparency, weak accountability, and insufficient integrity among government officials in preparing regional financial reports. These issues indicate that the quality of financial reporting is influenced not only by regulatory frameworks and accounting systems but also by the behavior and ethical values of public officials. This research employed a qualitative approach using a library research method. Data were collected from scholarly journals, books, and previous studies addressing behavioral accounting, prophetic values, regional financial management, and the Notes to the Financial Statements (CaLK). The data were analyzed descriptively through the processes of identifying, reviewing, and synthesizing relevant literature related to the research topic. The findings reveal that prophetic values namely siddiq (truthfulness), amanah (trustworthiness), tabligh (communicativeness), and fathanah (wisdom) play a significant role in fostering honest, responsible, transparent, and professional behavior among government officials in managing regional finances. These values also contribute to improving the quality of the preparation of the Notes to the Financial Statements (CaLK) as an essential instrument of public accountability. The study concludes that the internalization of prophetic values can support the realization of more transparent, accountable, and effective regional financial governance in accordance with the principles of good governance.